Capacity building in the rate of hospitalization of patients in times of crisis - Geravandi, Sahar; Tahery, Noorollah; Amiri, Homayoun; Afra, Arghavan; Soltani, Farhad; Shahriyari, Habib Allah; Jalali, Saeid; Javanmaerdi, Parviz; Mohammadi, Mohammad Javad (International Journal of Education and Cognitive Sciences, 2022)
Background: Considering the effects of crisis on society, emergency medicine and crisis management by scientifically and systematically observing crises and analyzing them, seeks to prevent and prepare for crisis and in case of its occurrence reduce the destructive effects and react quickly and appropriately. The purpose of this research study, capacity building in the rate of hospitalization of patients in times of crisis in Razi hospital, Ahvaz. Materials and Methods: This study was performed in Razi hospital, Ahvaz. In this study the amount of capacity at first emergency ward to providing medical services during before the crisis. Data was collected by crisis questionnaire Razi hospital and analyzed by descriptive statistics using EXCELL and SPSS. Results: The results of this study showed that capacity to accept were 14 injured in time of disasters in emergency ward at Razi teaching hospital, Ahvaz after increased capacity ability to accept injured in emergency ward increased to 38 persons. Conclusion: This study showed that it is necessary to take measures in order to hold periodic exercises and training courses, planning and providing facilities and equipment for crisis management.